1985
DOI: 10.1002/aic.690310211
|View full text |Cite
|
Sign up to set email alerts
|

A heat transfer model for tubes immersed in gas fluidized beds

Abstract: A model for local heat transfer between a gas‐fluidzed bed and a submerged tube is proposed based on combined dense‐phase and lean‐phase transport. The heat transfer process during dense‐phase contact at the tube surface is modeled by packet renewal mechanism and the transfer process during lean‐phase contact by fluid convection mechanism. The model predictions show good agreement with experimental local and average heat transfer coefficient data for horizontal tubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 41 publications
0
17
0
1
Order By: Relevance
“…. In this study, we use the general model of Kunii and Smith to calculate k pa , that is kpa=knormalgtrue[εpa+true(1εpatrue)ϕnormalk+2knormalg/3knormalstrue] where ϕ k is given by ϕnormalk=0.305true(knormalsknormalgtrue)0.25for 1knormalsknormalg1000 …”
Section: Resultsmentioning
confidence: 99%
“…. In this study, we use the general model of Kunii and Smith to calculate k pa , that is kpa=knormalgtrue[εpa+true(1εpatrue)ϕnormalk+2knormalg/3knormalstrue] where ϕ k is given by ϕnormalk=0.305true(knormalsknormalgtrue)0.25for 1knormalsknormalg1000 …”
Section: Resultsmentioning
confidence: 99%
“…18 The authors evaluated h B from experimental values of the total coefficient h by subtracting the solid and gas contributions in the dense phase. For estimating the bubble-phase heat transfer coefficient h B , the gas convective contribution (h c,B ) resulting from the own void plus the so called through flow, and the radiant contribution (h rad,B ) from the exchange between the surface and the solid particle at the bubble boundary should be considered.…”
Section: Evaluation Of Heat Exchange With the Bubble Phasementioning
confidence: 99%
“…There exist two distinct approaches (Mickley and Fairbanks, 1955;Botterill and Williams, 1963) for the prediction of the heat transfer coefficient. Many investigators have subsequently suggested modifications to the basic models cited above so as to achieve good agreement with experimental data (Saxena and Gabor, 1981;Chandran and Chen, 1985).…”
Section: Influence Of the Wall On Transient Conductionmentioning
confidence: 99%